(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
In this investigation, a pilot-scale fluidized magnetization roasting reactor was introduced and used to enhance magnetic properties of an iron ore. Consequently, the effects of roasting temperature, reducing gas CO flow rate and fluidizing gas N2 flow rate on the magnetization roasting performance was studied. The results indicate that the hematite are almost completely converted into magnetite by a gas mixture of 4 Nm3/h CO and 1 Nm3/h N2 at roasting temperature of 540 °C for about 30 s. Under the optimized conditions, a high grade concentrate containing 66.84% iron with an iron recovery of 91.16% was achieved. The XRD, VSM, and optical microscopy (OM) analyses revealed that most of the hematite, except some coarse grains, were converted to magnetite, and the magnetic properties were greatly enhanced.